Saint Kitts and Nevis. Significant achievements 2017 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2018)
The main activities carried out by the Institute in Saint Kitts and Nevis during 2017 are identified, with respect to the needs and interests of the country, strengthening issues such as beekeeping, innovation, governance, imports, technology, greenhouses, mango production, pork meat, health and safety and resilience against climate change. Likewise, work was done on microbiology, parasitology, animal and veterinary health, hydroponics, electronic commerce and product labeling. Finally, he supported himself in attending to clinical pathologies and in emergency care caused by the hurricanes.